2021
DOI: 10.1007/s00101-021-01037-z
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Pandemie: Präferenzen und Barrieren für die Disseminierung von Evidenzsynthesen

Abstract: Zusammenfassung Hintergrund Das COVID-19-Evidenz-Ökosystem (CEOsys) identifiziert, bewertet und fasst Ergebnisse wissenschaftlicher Studien in Evidenzsynthesen im Kontext von COVID-19 zusammen. Diese Evidenzsynthesen werden genutzt, um konkrete Handlungsempfehlungen abzuleiten und Leitlinien zu erstellen. Zielsetzung Vorbereitung der am besten geeigneten Verteilung von Evidenzsynthesen im Rahmen der Aufgaben des CEOsys-Projekts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…A major source of information for physicians was professional journals (online and print), whereas non-physicians consulted this source of information less. Overall, consistent with the results from our studies in intensive care staff [21,22], it can be seen that physician HCWs accessed professional, scientific sources to learn about COVID-19 significantly more than non-physician HCWs.…”
Section: Information Channelssupporting
confidence: 89%
See 4 more Smart Citations
“…A major source of information for physicians was professional journals (online and print), whereas non-physicians consulted this source of information less. Overall, consistent with the results from our studies in intensive care staff [21,22], it can be seen that physician HCWs accessed professional, scientific sources to learn about COVID-19 significantly more than non-physician HCWs.…”
Section: Information Channelssupporting
confidence: 89%
“…HCWs in hospitals, practices, and public health authorities consulted a wide range of dissemination channels when seeking relevant information for their daily decision-making. As in our previous studies among intensive care professionals [21,22], this study revealed substantial differences in the use of information sources on COVID-19 between non-physician and physician HCWs. Interestingly, fewer significant differences were found between HCWs in patient care and non-patient care (i.e., public health).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations